WHO classification of meningiomas–A single institutional experience (2020)
Introduction Meningiomas are among the most common intracranial neoplasms worldwide. The World Health Organization (WHO) has classified the neoplasm into three grades, with each grade having several histological variants. Several studies conducted in Black populations have shown differences compared with Caucasian populations regarding the occurrence of histological variants. Our study sought to examine the histological variants of meningioma seen in a predominantly Black population using the WHO grading system. Methods We conducted a retrospective study of all meningiomas seen in our hospital facility over a twenty-year period. Data from all patients diagnosed with meningioma, who also had surgical biopsies taken, were analyzed. The meningiomas were graded using the WHO grading system and classified into different histological variants within each grade as described by the WHO study group. Results The study included a total of 163 biopsies. There were more females diagnosed with meningiomas, with a female-to-male ratio of 1.4. Most of the tumors were grade one; however, there were more males with malignant meningiomas. Transitional meningiomas were the most commonly seen variants among the grade one tumors, while atypical and anaplastic variants were most common in grades two and three, respectively. Conclusion A larger population-based study is needed to provide epidemiological data on the occurrence of meningiomas in Black populations.